Online integrity disclosure: benchmark for good governance? / Corina Joseph ... [et al.] - Joseph, Corina; Madi, Nero; Janggu, Tamoi; Rahmat, Mariam; Mohamed, Nafsiah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
The objective of the paper is to determine the extent of integrity framework information disclosure on Malaysian local authorities’ websites using the coercive isomorphism tenet. The content analysis on 149 Malaysian local authorities’ websites had been conducted. The integrity framework disclosure index consists of 47 items that had been used to examine the level of integrity information disclosure on the websites. The level of integrity framework disclosure on the websites was low, possibly due to the low level of coercive pressures on the integrity initiative implementation. The findings would assist in helping the regulatory authorities and policy makers to strengthen their mechanisms in upholding integrity. There is little published research that examines the level of integrity framework disclosure in developing countries, such as Malaysia. This research used the institutional theory of isomorphism mechanism, namely, coercive to enhance the understanding of integrity framework disclosure and add to the pool of literature.